Comparative investigation of the detective quantum efficiency of direct and indirect conversion detector technologies in dedicated breast CT - Kuttig, Jan; Steiding, Christian; Kolditz, Daniel; Hupfer, Martin; Karolczak, Marek; Kalender, Willi Alfred (Physica Medica, 2015)
To investigate the dose saving potential of direct-converting CdTe photon-counting detector technology for dedicated breast CT.We analyzed the modulation transfer function (MTF), the noise power spectrum (NPS) and the detective quantum efficiency (DQE) of two detector technologies, suitable for breast CT (BCT): a flat-panel energy-integrating detector with a 70 ?m and a 208 ?m thick gadolinium oxysulfide (GOS) and a 150 ?m thick cesium iodide (CsI) scintillator and a photon-counting detector with a 1000 ?m thick CdTe sensor.The measurements for GOS scintillator thicknesses of 70 ?m and 208 ?m delivered 10% pre-sampled MTF values of 6.6 mm(-1) and 3.2 mm(-1), and DQE(0) values of 23% and 61%. The 10% pre-sampled MTF value for the 150 ?m thick CsI scintillator 6.9 mm(-1), and the DQE(0) value was 49%. The CdTe sensor reached a 10% pre-sampled MTF value of 8.5 mm(-1) and a DQE(0) value of 85%.The photon-counting CdTe detector technology allows for significant dose reduction compared to the energy-integrating scintillation detector technology used in BCT today. Our comparative evaluation indicates that a high potential dose saving may be possible for BCT by using CdTe detectors, without loss of spatial resolution.
EVALuna2:10106